The Amino-Terminal Part of the Needle-Tip Translocator LcrV of Yersinia pseudotuberculosis Is Required for Early Targeting of YopH and In vivo Virulence - Ekestubbe, Sofie; Bröms, Jeanette E.; Edgren, Tomas; Fällman, Maria; Francis, Matthew S.; Forsberg, Åke (Frontiers in Cellular and Infection Microbiology, 2016)
Type III secretion systems (T3SS) are dedicated to targeting anti-host effector proteins into the cytosol of the host cell to promote bacterial infection. Delivery of the effectors requires three specific translocator proteins, of which the hydrophilic translocator, LcrV, is located at the tip of the T3SS needle and is believed to facilitate insertion of the two hydrophobic translocators into the host cell membrane. Here we used Yersinia as a model to study the role of LcrV in T3SS mediated intracellular effector targeting. Intriguingly, we identified N-terminal lcrV mutants that, similar to the wild-type protein, efficiently promoted expression, secretion and intracellular levels of Yop effectors, yet they were impaired in their ability to inhibit phagocytosis by J774 cells. In line with this, the YopH mediated dephosphorylation of Focal Adhesion Kinase early after infection was compromised when compared to the wild type strain. This suggests that the mutants are unable to promote efficient delivery of effectors to their molecular targets inside the host cell upon host cell contact. The significance of this was borne out by the fact that the mutants were highly attenuated for virulence in the systemic mouse infection model. Our study provides both novel and significant findings that establish a role for LcrV in early targeting of effectors in the host cell.